2010
DOI: 10.1016/j.fct.2010.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress parameters in rats exposed to fluoride and caffeine

Abstract: SUMMARY:The action of fluoride (F) and aspirin (acetylsalicylic acid, ASA) administered separately and together on oxidative stress parameters and on F excretion in rats was studied over a period of six weeks. Thirty adult male Wistar rats were divided into five equal groups of six each: (I) controls receiving tap water; (II) controls receiving intragastrically 1 mL of tap water (once a day); (III) animals receiving 25 mg F/L in their drinking water; (IV) animals receiving 35 mg ASA/kg bw/ day; (V) animals rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 30 publications
4
36
0
Order By: Relevance
“…The present study clearly reveals that excessive accumulation of fluoride interfere with structural and functional integrity of the developing nervous system through generation of oxidative stress, leading to alter neuronal integrity. Several studies (Chirumari & Reddy 2007;Inkielewicz & Czanowski 2008;Murali & Panneerselvam 2007;Shivashankara et al 2000;Vani & Reddy 2000) suggest similar results and corroborate the present findings. The detoxification of xenobiotics lead to natural deficit of certain vital nutrients/antioxidants and further risk caused by the increased environmental insults that induce oxidative stress.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The present study clearly reveals that excessive accumulation of fluoride interfere with structural and functional integrity of the developing nervous system through generation of oxidative stress, leading to alter neuronal integrity. Several studies (Chirumari & Reddy 2007;Inkielewicz & Czanowski 2008;Murali & Panneerselvam 2007;Shivashankara et al 2000;Vani & Reddy 2000) suggest similar results and corroborate the present findings. The detoxification of xenobiotics lead to natural deficit of certain vital nutrients/antioxidants and further risk caused by the increased environmental insults that induce oxidative stress.…”
Section: Resultssupporting
confidence: 82%
“…In vivo studies confirm that the fluoride ion is strongly reactive due to its high negative charge density and alter the distribution of electrons, including enzymes and membrane transport proteins, thereby affecting the metabolites of many cells, tissues and organs (Korkmaz 2000). In advanced stages of fluorosis, neurological manifestations such as paralysis of limbs, vertigo, spasticity in extremities and impaired mental acuity are observed in humans (Inkielewicz & Czanowski 2008;Inkielewicz & Krechniak 2004;Mullenix et al 1995).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Chronic fluoride intoxication or fluorosis has been shown to be associated with a manifestation of neurological dysfunctions in humans and experimental animals (Shivarajashankara et al, 2001). It has also been demonstrated that one of the various mechanisms of fluoride-induced injury of the central nervous systems is attributed to oxidative stress in neural cells (Inkielewicz & Czanowski, 2008). Moreover, reports from various laboratories established a close correlation between oxidative stress in animals and fluoride intoxication (Bhatnagar et al, 2002;Shivashankara et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Abreu et al, [55] found that the consumption of coffee decreased the lipid peroxidation of the membranes; increased the concentration of glutathione, a potent endogenous antioxidant; and increased the activity of two antioxidant enzymes, glutathione reductase and superoxide dismutase. Undoubtedly, these beneficial effects of coffee on antioxidant properties are partly due to caffeine, kahweol and cafestol [56][57][58]. In addition to the effect of coffee, cardamom also have a potential antioxidants such as 1, 8-ceineoil and alphaterpineol, protocatechualdehyde and protocatechuic acid which have health benefits by inhibiting lipid peroxidation and activation of antioxidant enzymes [24,25].…”
Section: Essential Oil %mentioning
confidence: 99%